Аналогия переноса теплоты и количества движения в каналах с поверхностными генераторами вихрей - Халатов, А.А.; Онищенко, В.Н.; Борисов, И.И. (Видавничий дім "Академперіодика" НАН України, 2007)
The survey of the experimental data on the Reynolds analogy factor in channels with surface spherical indentations (dimples) is given. Four different groups of dimpled rectangular channels under turbulent flow conditions are analyzed. As shown, only channel with one or two dimpled walls with no cross-section blockage provides the Reynolds analogy factor to be more than the unity.